Esterified sterols and their contribution to the total sterols in edible mushrooms - Hammann, Simon; Lehnert, Katja; Vetter, Walter (Journal of Food Composition and Analysis, 2016)
Mushrooms are a valued source of sterols, which can be present in free form and esterified to fatty acids. In addition to the principal ergosterol, several minor sterols occur. Ergosterol and ergosteryl ester were determined directly by gas chromatography coupled to mass spectrometry (GC/MS) in the trimethylsilylated lipid extract of each six samples of button mushrooms, oyster mushrooms, king trumpet mushrooms and shiitake. Free ergosterol was highest in button mushrooms 415–544 mg/100 g dry matter (d.m.) and lowest in oyster and king trumpet mushrooms (<350 mg/100 g d.m.). On the other hand, concentrations of ergosteryl esters were significantly lower (5–26 mg/100 g d.m.) in all mushroom samples. The distribution of minor sterols (most importantly ergosta-7,22-dienol, ergosta-5,7-dienol, ergosta-7-enol) between free and esterified form was determined after group separation with solid phase extraction. Higher proportions of the minor sterols were found esterified to fatty acids and ergosta-7-enol was found predominantly (70%) in this form in oyster mushrooms and shiitake. The minor sterols ergosta-8,24(241)-dienol, ergosta-8-enol and 7-dehydro-poriferasterol could be tentatively identified in the samples based on GC/MS data. In addition, four sterols were found only in the steryl ester fraction of the mushroom samples.
Keywords: Pleurotus ostreatus; Steryl ester; Basidiomycete; Agaricus bisporus; Gas chromatography; Ergosterol; Mass spectrometry; Lentinus edodes; Pleurotus eryngii; Mushroom